ANALISIS PENERAPAN PASAL 14 AYAT (1) UNDANG-UNDANG NOMOR 1 TAHUN 1946 TENTANG PERATURAN HUKUM PIDANA DAN PASAL 45A AYAT (2) UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERHADAP KASUS PENYEBARAN BERITA BOHONG DI MEDIA SOSIAL (STUDI KASUS: PUTUSAN PENGADILAN NOMOR 277/PID.SUS/2019/PT.DKI) - Sonia Christy Sipayung; R Rahaditya (Jurnal Hukum Adigama, 2021)
Social media can provide positive benefits, but on the other hand it also provides opportunities to be used as a medium for committing criminal acts such as spreading false news. Fake news (hoax) is information that is covered up as if the news is fact. This study aims to find out how the urgency of the implementation of Article 14 clause (1) of Law Number 1 of 1946 concerning Criminal Law Regulations and Article 45A clause (2) of Law Number 19 of 2016 concerning Electronic Information and Transactions is associated with cases of spreading false news. on social media in the case of the Court's decision Number 277/PID.SUS/2019/PT.DKI. The method used is normative legal research. From the analysis of this writing, it is known that there are differences in the elements of the two articles. These elements must be met in the evidence at trial accompanied by the evidence provided for in Article 184 clause (1) of Law Number 8 of 1981 concerning the Criminal Procedure Code, which consists of witness statements, expert witness statements, letters, instructions, and the defendant's statement.